Towards new approaches for converting principles of vernacular architecture into energy efficient buildings in hot and dry climates - Lavafpour .Y,; Surat .M, (Penerbit UKM, 2011)
Buildings can be designed to require far less than the energy of today's average. Reducing energy consumption of buildings in hot-dry climates by using natural energy sources to provide comfortable microclimate is the main concern of this study. In this paper design strategies in terms of energy efficiency is considered based on proper building form, material selection and orientation and by taking advantages of passive cooling strategies and ventilation. The study aims to show that the idea of using natural energy and passive cooling strategies came from the vernacular principles